Undisruptable or stable concepts: can we design concepts that can avoid conceptual disruption, normative critique, and counterexamples? - Lundgren, Björn (Ethics and Information Technology, 2024)
It has been argued that our concepts can be disrupted or challenged by technology or normative concerns, which raises the question of whether we can create, design, engineer, or define more robust concepts that avoid counterexamples and conceptual challenges that can lead to conceptual disruption. In this paper, it is argued that we can. This argument is presented through a case study of a definition in the technological domain.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Conceptual counterexamples; Conceptual disruption; Conceptual engineering; Normative critique of concepts; Stable concepts; Undistruptable concepts